TAFSIR MAUDHU’I SURAT AL-QARI’AH - Karomi, Ahmad (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2018)
One of the sura in the Quran that tells of the doomsday is the sura of Qariah. The scholars agree that this sura of Qariah is revealed in Mecca. This letter begins by recounting the doom of the Day of Judgment, ruffling the whole world and ending with the news held it charity scales that serve as a barometer of good and bad human charity. If the scales of good deeds are heavy, then he goes to heaven. If the scales are worth a little, then he goes to hell. This paper tries to examine the letter of Qariah more deeply.Keywords: tafseer, sura, maudlu’i, Qariah